PENGARUH BIOLARVASIDA DAUN TANAMAN SEBAGAI KONTROL VEKTOR NYAMUK AEDES AEGYPTI PENYEBAB DEMAM BERDARAH: A LITERATURE REVIEW - Sidik Maulana (Jurnal Medika Hutama, 2021)
Background. Currently, vaccines and drugs have not been found to prevent and eliminate viruses, thus to prevent Dengue Hemorrhagic Fever (DHF) the most effective is to eradicate the larvae. Abatization and temefos are the control of mosquito larvae by causing environmental pollution and insect resistance to them. Hance, more effective efforts are needed and do not cause problems or environmental damage, one of which is natural larvicides or biolarvicides derived from plants, especially leaf parts by considering cost-effectiveness. Aim. Know the effect of various leaves as biolarvicide to Aedes aegypti cause DHF. Method. Literature review through publication articles 2016-2020 from the electronic database of Garuda Dikti and CINAHL (Ebsco). Result. Leaves that have the effect of killing the Aedes aegypti larvae are the leaves of tumih, papaya, betel, binjai, soursop, tobacco, and lime with an average concentration of less than or equal to 50% (<LC50). Ingredients or substances that have a larvicidal effect on leaves include alkaloids, tannins, phenolics, saponins, flavonoids and steroids, essences, flavonoids, alkaloids, terpenoids, phenols, organic acids (stearic acid and palmitic acid), triterpenoids, limonoids, and nicotine. Conclusion. Only a few plant leaves have been shown to be effective or influential as biolarvicides with a concentration of LC50. The authors recommend that plants that are proven to be effective can be used as resources that can be utilized by the community which have been proven effective as biolarvicides.